2015
DOI: 10.1515/fhort-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

The influence of biodegradable mulches on the yielding of autumn raspberry (Rubus idaeus L.)

Abstract: A three-year experiment was set up to assess the effect of three mulch types on the growth and yield of 'Polka' autumn fruiting raspberry (Rubus idaeus L.). The experimental arrangement comprised four combinations of two parallel blocks, one of which was a field crop and the second was a covered crop in the form of a high tunnel with raised beds sides. The crop was grown on raised beds (approximately 30 cm high) covered with a mulch made of: 1) polypropylene non-woven (PP); 2) PP with a photodegradant; 3) poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…Both Trinka and Pritts (1992) and Zhang et al (2019) reported plastic mulches increased primocane height in comparison with no-mulch treatments. Plants grown in BDMtreated plots had primocane heights similar to the BG plots, which was inconsistent with what has been observed in past studies (Kr ol-Dyrek and Siwek, 2015;Tecco et al, 2016;Zhang et al, 2019). This discrepancy was likely because of the early removal of BDMs (Mar.…”
Section: Discussioncontrasting
confidence: 79%
“…Both Trinka and Pritts (1992) and Zhang et al (2019) reported plastic mulches increased primocane height in comparison with no-mulch treatments. Plants grown in BDMtreated plots had primocane heights similar to the BG plots, which was inconsistent with what has been observed in past studies (Kr ol-Dyrek and Siwek, 2015;Tecco et al, 2016;Zhang et al, 2019). This discrepancy was likely because of the early removal of BDMs (Mar.…”
Section: Discussioncontrasting
confidence: 79%
“…Data on yield and crop quality were evaluated and presented in a separate publication by Król-Dyrek and Siwek (2015). Explanations as in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…compared to the open field has also been reported for the primocane-type raspberry 'Polka' in Poland (Król-Dyrek and Siwek, 2015). Norwegian researchers have reported SS contents of 8.3% for 'Glen Ample' in the open field (61°11'N) (Mazur et al, 2014a) and, in another study, 9.5% in a polyethylene tunnel (59°40'N) (Remberg et al, 2010).…”
Section: Discussionmentioning
confidence: 68%
“…Usually warm and dry weather increases sugar content and decreases acidity in raspberry fruit (Jennings, 1988;Malowicki et al, 2008). However, lower sugar content was observed in the primocane-type raspberry 'Polka' fruit when grown in high tunnels compared to an open field environment (Król-Dyrek and Siwek, 2015). This study indicates parameters other than the temperature difference between the tunnel and open field influenced this quality trait.…”
mentioning
confidence: 77%